First Determination in the Extended Corona of the 2D Thermal Evolution of a Current Sheet after a Solar Eruption - Alessandro Bemporad; Guanglu Shi; Shuting Li; Beili Ying; Li Feng; Jun Lin; Lucia Abbo; Vincenzo Andretta; Aleksandr Burtovoi; Vania Da Deppo; Yara De Leo; Silvano Fineschi; et al. (The Astrophysical Journal, 2024)
For the first time the evolution of the coronal reconfiguration after a coronal mass ejection (CME) was observed by the multichannel Metis Coronagraph on board the ESA–Solar Orbiter mission. The images acquired in visible light (VL) between 3.0 and 5.4 R _⊙ show the formation after a CME of a bright elongated radial feature interpreted as a post-CME current sheet (CS). The unique combination of VL and UV images allowed the time evolution of multiple plasma physical parameters inside and outside the CS region to be mapped in 2D for the first time. The CS electron temperature reached peak values higher than 1 MK, more than twice as high as the surrounding corona. An elongated vertical diffusion region, characterized as a region of much higher thermal pressure and lower magnetic pressure, is observed to slowly propagate outward during 13 hr of observations. Inside this region the Alfvénic Mach number is of the order of M _A ≃ 0.02–0.11, the plasma β is close to unity, and the level of turbulence is higher than in the surrounding corona, but decreases slowly with time. All these results provide one of the most complete pictures of these features, and support the idea of a magnetic reconnection coupled with turbulence, thus allowing significant heating of the local plasma, despite the weakness of involved coronal magnetic fields in the considered altitude range.